Isolation and characterization of extreme halophilic bacterium Salinicoccus sp. JAS4 producing extracellular hydrolytic enzymes - Y, Jayachandra S; S, Anil Kumar; P, Merley D; B, Sulochana M (Recent Research in Science and Technology, 2012)
A extreme halophilic bacterium, strain JAS4 was isolated from the Arabal soil of west coast of Karnataka, India. The isolate is Gram positive, strictly aerobic, ferments several carbohydrates and has motile, coccoid shaped cells and non sporing, catalase- and oxidase- positive, that grew in presence of 2-25% (w/v) NaCl and at pH 6.5-11, with optimum growth at 10%(w/v) NaCl, with an optimum growth temperature of 340C, has potential to produce the extracellular enzymes such as Amylase, Protease, Inulinase and Gelatinase, but production of lipase was found to be negative. The phenotypic studies and genotypic analysis by 16S rRNA analysis showed that the bacterium belonged to the genera Salinicoccus of 98% BLAST sequence similarity and it is named as Salinicoccus sp. JAS4 and phylogenetic study was carried out using Mega5 software.